DAY-TRADERS WORKING IN STOCK MARKET & RISK PROFILE OF NONCOMMUNICABLE DISEASES - Saoji, Ajeet; Mitra, Arun; Saoji, Prachi; Hajare, Shilpa (International Journal of Clinical and Biomedical Research, 2017)
Background: A Day-trader who is involved typical working day. He/she would have to endure extremes of unpredictable market fluctuations placing them at a greater risk of non-communicable disease. The data regarding these health issues among day-traders working in stock market in India is deficient. Objectives: This study was devised with the aim of studying the risk profile among day-traders and compare them with a comparative group. Materials & Methods: A total of 128 (64 Day-traders; 64 IT-Professionals) were interviewed using the WHO-Steps Questionnaire. Proportions, Mean values, Odds ratio and p-values were calculated with the help of statistical package STATA version 14. Results: The overall mean age of the study participants was 42.24 ±6.61 with the mean age 41.78 ±5.16 and 42.7 ±7.82 respectively. The prevalence rates of alcohol use, tobacco use, inadequate physical activity and inadequate diet among day traders were 68.6%, 56.3%, 64% and 89% respectively. More than 50% were overweight or had abdominal obesity and more than three-fourths had high blood pressure. Conclusions: The burden of NCD risk factors was high in the study population compared to the national averages. The prevalence of risk factors was high in day-traders as compared to IT professionals. Use of tobacco and prevalence of obesity & hypertension were found to be high among day-traders. KEYWORDS: Stock market; Day-trader; Risk-profile; Non-communicable disease; WHO-STEPs approach.